Quantum tunneling of massive spin-1 particles from non-stationary metrics - Sakallı, İzzet; Övgün, Ali (General Relativity and Gravitation, Springer, 2015)
We focus on the HR of massive vector (spin-1) particles tunneling from Schwarzschild BH expressed in the Kruskal–Szekeres and dynamic Lemaitre coordinates. Using the Proca equation together with the Hamilton–Jacobi and the WKB methods, we show that the tunneling rate, and its consequence Hawking temperature are well recovered by the quantum tunneling of the massive vector particles.
The file in this item is the post-print version of the article (author’s copy; author’s final manuscript, accepted for publication after peer-review process). Due to copyright restrictions, the access to the publisher version (published version) of this article is only available via subscription. You may click URI (with DOI: 10.1007/s10714-015-1997-y) and have access to the Publisher Version of this article through the publisher web site or online databases, if your Library or institution has subscription to the related journal or publication.
Keywords: quantum tunneling; black holes; hawking radiation; general relativity; Regular coordinates; Proca equation; Massive vector particles